2016
DOI: 10.1096/fj.201600832r
|View full text |Cite
|
Sign up to set email alerts
|

IL‐10 prevents aging‐associated inflammation and insulin resistance in skeletal muscle

Abstract: Altered energy balance and insulin resistance are important characteristics of aging. Skeletal muscle is a major site of glucose disposal, and the role of aging-associated inflammation in skeletal muscle insulin resistance remains unclear. To investigate, we examined glucose metabolism in 18-mo-old transgenic mice with muscle-specific overexpression of IL-10 (M) and in wild-type mice during hyperinsulinemic-euglycemic clamping. Despite similar fat mass and energy balance, M mice were protected from aging-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 46 publications
4
75
0
1
Order By: Relevance
“…Older people also exhibit lower skeletal muscle insulin-stimulated Akt activity [59], impaired insulin signaling, and decreased skeletal muscle insulin sensitivity. In addition, skeletal muscle insulin sensitivity in aged mice is reduced, and insulin resistance occurs [24,84]. These data indicate that the glucose metabolism capacity of the skeletal muscle decreased and the risk of insulin resistance increased.…”
Section: Introductionmentioning
confidence: 93%
“…Older people also exhibit lower skeletal muscle insulin-stimulated Akt activity [59], impaired insulin signaling, and decreased skeletal muscle insulin sensitivity. In addition, skeletal muscle insulin sensitivity in aged mice is reduced, and insulin resistance occurs [24,84]. These data indicate that the glucose metabolism capacity of the skeletal muscle decreased and the risk of insulin resistance increased.…”
Section: Introductionmentioning
confidence: 93%
“…McAulty et al (61) found that the daily consumption of blueberries for 6 weeks elevated innate immune indices, including plasma IL-10. Furthermore, consumption of foods rich in anthocyanins has also been shown to increase the IL-10: TNFα ratio, promoting a shift toward an anti-inflammatory/antioxidant status (62)(63)(64)(65). Nutritional intervention studies targeting the amelioration of chronic inflammation found that administration of other polyphenolic compounds suppressed inflammation by creating an anti-inflammatory/antioxidant environment.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously at 3 days post injury IL-10 was upregulated in old but not young muscle and this trend was similar in LPS stimulated macrophages. This was initially surprising one may expect upregulation of an anti-inflammatory cytokine to be beneficial, and IL-10 is required for myogenesis post injury 21 and muscle-specific expression of IL-10 in aged muscle reduces inflammation and insulin resistance 28 . However, IL-10 does not directly act on myoblasts but instead induces polarization of muscle-macrophages to M2, which then induce myogenesis via changes to the microenvironment 21 .…”
Section: Discussionmentioning
confidence: 99%